Basilar Artery Thrombosis in a Child Treated With Intravenous Tissue Plasminogen Activator and Endovascular Mechanical Thrombectomy. (November 2013) - Fink, Jakob; Sonnenborg, Laura; Larsen, Line Lunde; Born, Alfred Peter; Holtmannspötter, Markus; Kondziella, Daniel
Basilar artery occlusion in children is rare. It has a high mortality and morbidity if recanalization is not achieved before extensive brainstem infarction has occurred. An 11-year-old boy presented with a clinical and radiological "top-of-the-basilar" syndrome. Intravenous tissue plasminogen activator was administered, and the patient was immediately referred to the regional stroke center. Subsequent mechanical thrombectomy using a Solitaire stent (Solitaire FR stent; ev3, Irvine, CA, USA) resulted in clot removal and recanalization of the basilar artery 4 hours after stroke onset. The patient made a full clinical recovery. To the authors' knowledge this is the first report on basilar artery occlusion in a child treated with "bridging" therapy, the combination of intravenous thrombolysis and endovascular thrombectomy. If the diagnosis can be made within the time window for intravenous thrombolysis (4.5 hours), the present case suggests that bridging therapy in pediatric basilar artery occlusion can be safe and effective.